Bad Cops at Home: An Exploratory Study of Officer-Involved Domestic Violence - Liederbach, John (2011)
Officer-involved domestic violence is a problem that should concern researchers, policymakers, the policing community, and the general public. Yet there is very little research in the area and no official data is available to discern the nature and prevalence of domestic violence in police families. Victims are reluctant to report officer-involved domestic violence and often feel helpless in the criminal justice system where the abuser is employed. This is complicated by provisions of the Lautenberg Amendment of 1996 which prohibit anyone convicted of a crime of domestic violence from carrying a firearm. This study explores 324 cases of state and local police officers from agencies across the United States arrested during 2005-2007 for crimes involving family violence. The analysis includes an examination of preferential charging decisions in cases of officer-involved domestic violence, as well as other factors including case and employment outcomes